2022
DOI: 10.1016/j.jaip.2021.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Esophagitis Patients Are Not at Increased Risk of Severe COVID-19: A Report From a Global Registry

Abstract: What is already known about this topic? No data has been published on the outcome of coronavirus disease 2019 in eosinophilic esophagitis (EoE)/eosinophilic gastrointestinal disease (EGID) patients.What does this article add to our knowledge? COVID-19 severity in EoE patients appears to be comparable to that of the general population.How does this study impact current management guidelines? EoE/EGID patients with COVID-19 may be managed following guidelines for the general population.BACKGROUND: The impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…No patient died. One patient had an EGID flare 17 . The authors concluded that patients with EGIDs may not have an increased risk of severe COVID‐19 and that COVID‐19 does not lead to EGID flares 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No patient died. One patient had an EGID flare 17 . The authors concluded that patients with EGIDs may not have an increased risk of severe COVID‐19 and that COVID‐19 does not lead to EGID flares 17 …”
Section: Discussionmentioning
confidence: 99%
“…17 The authors concluded that patients with EGIDs may not have an increased risk of severe COVID-19 and that COVID-19 does not lead to EGID flares. 17 Although no clear associations between severe outcomes of COVID-19 and EGDIs were identified in the current study or in previous reports, this study has several strengths. First, the study period included the vaccination era.…”
Section: Discussionmentioning
confidence: 99%
“…EoE is a chronic condition, and upper endoscopy is important for monitoring endoscopic and histologic response, and for performing esophageal dilations in patients with strictures or narrowing. The COVID-19 pandemic has not only had a direct impact on patients with EoE and on GI practice in general [ 14 20 , 23 ], but indirect impacts are likely though not yet extensively studied. The goal of our study, therefore, was to determine the impact of endoscopic procedure cancellations due to COVID-19 on outcomes in our EoE patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with EGIDs have not been found to have an increased risk of COVID-19 infection or complications [ 20 25 ]. This may be due to patients with eosinophilic gastrointestinal disorders having reduced RNA levels of Angiotensin Converting Enzyme (ACE) type 2 and serine protease TMPRSS2, both important mediators for SARS-CoV-2 entry into host cells [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas eosinophils may be associated with disease pathogenesis in COVID-19 infection, pre-existing eosinophilic conditions do not appear to be a risk factor for severe illness 60 , 61 . In fact, some studies have suggested that type 2 inflammation may exert a protective effect by limiting viral entry through modulation of angiotensin-converting enzyme 2 (ACE2) expression at respiratory and gastrointestinal (GI) epithelial surfaces 62 66 .…”
Section: Eosinophils and The Antiviral Responsementioning
confidence: 96%